Leptin Signaling in the Ovary of Diet-Induced Obese Mice Regulates Activation of NOD-Like Receptor Protein 3 Inflammasome - Adamowski, Marek; Wołodko, Karolina; Oliveira, Joana; Castillo-Fernandez, Juan; Murta, Daniel; Kelsey, Gavin; Galvão, António M. (Frontiers in Cell and Developmental Biology, 2021)
Obesity leads to ovarian dysfunction and the establishment of local leptin resistance. The aim of our study was to characterise levels of Nod-Like Receptor Protein 3 (NLRP3) inflammasome activation during obesity progression in the mouse ovaries and liver and test the putative role of leptin on its regulation. C57BL/6J mice were treated with equine chorionic gonadotropin (eCG) or human chorionic gonadotropin (hCG) for oestrous cycle synchronisation and ovaries collection. In diet-induced obesity (DIO) model, mice were fed chow diet (CD) or high fat diet (HFD) for 4 or 16 weeks (wk), whereas in hyperleptinemic model (LEPT), mice were injected with leptin for 16 days (16L) or saline (16C) and in the genetic obese leptin-deficient ob/ob (+/? and -/-) animals were fed CD for 4wk. Either ovaries and liver were collected, as well as cumulus cells (CCs) after superovulation from DIO and LEPT. In DIO protocol, protein expression of NLRP3 inflammasome components was increased in 4wk HFD, but decreased in 16wk HFD. Moreover LEPT and ob/ob models revealed NLRP3 and IL-1 upregulation in 16L and downregulation in ob/ob. Transcriptome analysis of CC showed common genes between LEPT and 4wk HFD modulating NLRP3 inflammasome. Moreover analysis in the liver showed upregulation of NLRP3 protein only after 16wk HFD, but also the downregulation of NLRP3 protein in ob/ob-/-. We showed the link between leptin signalling and NLRP3 inflammasome activation in the ovary throughout obesity progression in mice, elucidating the molecular mechanisms underpinning ovarian failure in maternal obesity.